2009
DOI: 10.1115/1.3066345
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Testing of Gerotor and Scroll Expanders Used in, and Energetic and Exergetic Modeling of, an Organic Rankine Cycle

Abstract: This paper presents the experimental testing of relatively cost-effective expanders in an organic Rankine cycle (ORC) to produce power from low-grade energy. Gerotor and scroll expanders were the two types of expanders tested to determine their applicability in producing power from low-grade energy. The results of the experimental testing showed that both types of expanders were good candidates to be used in an ORC. The gerotor and scroll expanders tested produced 2.07 kW and 2.96 kW, and had isentropic effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 7 publications
2
33
0
2
Order By: Relevance
“…This value resulted equal to 0.29, as a consequence of the imposed flank gap between the fixed and the moving profiles. This value is comparable to similar results found in literature [24].…”
Section: Volumetric Efficiencysupporting
confidence: 95%
“…This value resulted equal to 0.29, as a consequence of the imposed flank gap between the fixed and the moving profiles. This value is comparable to similar results found in literature [24].…”
Section: Volumetric Efficiencysupporting
confidence: 95%
“…Sprawia to, Ŝe świetnie nadają się do zastosowania w układach chłodniczych, klimatyzacyjnych (takŜe w klimatyzatorach samochodowych), jak równieŜ w obiegach pomp ciepła. Dodatkowo, nowym polem zastosowań jest wykorzystywanie maszyn spiralnych jako rozpręŜarek w układach ORC [3,4]. Zasada działania spręŜarki spiralnej (rys.…”
Section: Wprowadzenieunclassified
“…Oliveira (2007) provides an example layout of a combined heat and power solar thermal system which utilises a Rankine cycle to produce work from solar heat, and recovers useful heat from the condenser. Mathias et al (2009) uses a simple non-regenerative ORC with a scroll expander to produce an isentropic efficiency as high as 83%. It is demonstrated that the highest isentropic efficiency is attained when both the specific volume ratio of the fluid undergoing expansion is matched to the built-in volume ratio of the expander, and when the volume flow rate is matched to the rotational speed.…”
Section: Conclusion Section 37 51mentioning
confidence: 99%
“…The expander performs at between 57% and 59% isentropic efficiency for all months of the year. This is a respectable efficiency for a power expander, however, isentropic efficiencies of up to 83% have been reported in the literature (Clemente et al, 2011;Mathias et al, 2009;Oudkerk et al, 2011). Greater isentropic, and therefore system, efficiency might be achieved by using a similar sized scroll expander that has been purpose-built for expansion.…”
mentioning
confidence: 94%
See 1 more Smart Citation